2012
DOI: 10.1016/j.physbeh.2011.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Feeding behaviour after injection of α-adrenergic receptor agonists into the median raphe nucleus of food-deprived rats

Abstract: This study investigated the participation of median raphe nucleus (MnR) α1-adrenergic receptors in the control of feeding behaviour. The α1-adrenergic agonist phenylephrine (PHE) and α2-adrenergic agonist clonidine (CLON) (at equimolar doses of 0, 6 and 20 nmol) were injected into the MnR of: a) rats submitted to overnight fasting (18 h); or b) rats maintained with 15 g of lab chow/day for 7 days. Immediately after the drug injections, the animals were placed in the feeding chamber and feeding and non-ingestiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Thus, it is possible that activation of DR α-1 adrenoceptors by PHE results in 5-HT release in fasted animals, since facilitatory control of 5-HT release is attributed to these receptors (Bortolozzi and Artigas, 2003). In agreement with this suggestion, a study demonstrated that PHE injections into the median raphe nucleus (MR), another major serotonergic cell group with α-adrenoceptors (Adell and Artigas, 1999), also evoked hypophagia in fasted rats (Ribas et al, 2012). Also, serotonergic activity is low in food restricted rats and, especially in the DR, food restriction decreases the optical density of 5-HT positive neurons when compared to fed rats (Haider and Haleem, 2000;Kang et al, 2001).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Thus, it is possible that activation of DR α-1 adrenoceptors by PHE results in 5-HT release in fasted animals, since facilitatory control of 5-HT release is attributed to these receptors (Bortolozzi and Artigas, 2003). In agreement with this suggestion, a study demonstrated that PHE injections into the median raphe nucleus (MR), another major serotonergic cell group with α-adrenoceptors (Adell and Artigas, 1999), also evoked hypophagia in fasted rats (Ribas et al, 2012). Also, serotonergic activity is low in food restricted rats and, especially in the DR, food restriction decreases the optical density of 5-HT positive neurons when compared to fed rats (Haider and Haleem, 2000;Kang et al, 2001).…”
Section: Discussionmentioning
confidence: 78%
“…Statistical analyses revealed that PHE 20 nmol injection in the xscp did not affect ingestive behaviors when compared to the intra-DR vehicle group ( Figures 3C,D ). Previous work reported that PHE injection of 20 nmol dose into median raphe nucleus (MR) decreased food intake in fasted rats ( Ribas et al, 2012 ). Thus, the effects on food intake could be the sum of the drug effects in these two nuclei due the close localization in the mesopontine tegmentum.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, CBG-induced hyperphagia may be mediated by its activity (to date only observed in vitro) as a highly potent agonist of α2-adrenoceptors (Cascio et al 2010 ). Consistent with this, stimulation of α2-adrenoceptors in the hypothalamic paraventricular nucleus has been shown to have hyperphagic effects in satiated rats (Wellman et al 1993 ; Taksande et al 2011 ), whilst administration of the α2-adrenoceptor agonist clonidine into the median raphe nucleus had orexigenic effects in free feeding (Mansur et al 2010 ) but not fasted or food-restricted rats (Ribas et al 2012 ). Whilst the above studies suggest that central α2-adrenoceptor activation may be involved in the hyperphagic activity of CBG, it should be noted that recent cardiovascular safety assays in dog did not reveal any effects on cardiovascular parameters (T. Hill, personal communication), indicating that α2-adrenoceptor agonism may not be the predominant action for CBG.…”
Section: Discussionmentioning
confidence: 86%